Seroprevalencia de Brucelosis en el Personal que Labora en Camales del Departamento Lambayeque.Junio 2014-Febrero 2015 - Santa Cruz López, Cinthya Yanina (2015)
Brucellosis is a zoonosis of worldwide distribution, which represents a real occupational hazard for butchers, butchers, farmers, veterinarians and laboratory personnel, among others. In this research the seroprevalence of brucellosis and predisposing factors in slaughterhouses personnel working in the department of Lambayeque, from June 2014 to February 2015 was determined.To do a random sampling, obtaining blood samples by venipuncture 131 of the 27 municipal slaughterhouses Lambayeque department was made. To determine the presence of antibodies to Brucella sp. tests and Rose Bengal antigen used Huddlenson obtaining a prevalence of 10,7%.As for the determination of predisposing factors, a survey (on consumption of fetuses derived from slaughtered animals, accidents during the massacre) was applied and found that there is a relationship between the consumption of blood and the presence of antibodies against Brucella sp. in the slaughterers. In addition, it was found that 83,5% of the slaughterhouses did not provide proper hygienic conditions, 26,7% of workers did not use any protection during the work of killing (wearing gloves, apron, boots, masks); what constitutes an occupational risk factor for the spread of Brucella sp.